Application of green tea waste with fibrolytic enzyme and phytase on layer performance and egg quality - Chumkam, S.; Jintasataporn, O.; Triwutanon, S. (Diponegoro University, 2021)
This study aimed to investigate the effect of green tea waste, fibrolytic enzymes (xylanase and cellulase) and phytase supplementation in layer diets on performance and egg quality. The experiment was assigned in a 2×3 factorial arrangement by completely randomized design. Factor A consisted of two types of diets: a) a basal diet without any green tea waste and b) a basal diet with 1% of green tea waste. Factor B consisted of three levels of enzymes: a) level 0X, no enzyme supplementation; b) level 1X, a combination of fibrolytic enzymes, 24,000 FAXU xylanase and 100 ECU cellulase, and 1,000 FTU phytase; and c) level 2X, combination of fibrolytic enzymes, 48,000 FAXU xylanase and 200 ECU cellulase, and 2,000 FTU phytase. One hundred and ninety- two Roman Brown hens, aged 52 weeks, were randomly distributed to six groups and four replications. Layer hens were fed commercial diets with green tea waste and fibrolytic enzymes added on top as assigned in the treatment. The results showed that green tea waste significantly increased (p<0.05) egg production, egg mass, feed conversion, and Haugh unit. In addition, green tea waste tended to affect (p=0.07) TBAs value. Furthermore, the enzyme level significantly decreased (p<0.05) feed intake and TBAs value. In conclusion, the supplementation of 1% of green tea waste and 2X enzymes can improve feed conversion and the antioxidative property of eggs.